Peralihan Hak Atas Harta Warisan Kepada Ahli Waris yang Dikuasai Secara Sepihak oleh Keluarga Pewaris - Wanda Shicilya; I Nyoman Putu Budiartha; Diah Gayatri Sudihya (Fakultas Hukum Universitas Warmadewa, 2022)
Indonesia has an inheritance system consisting of inheritance elements, which include heirs, heirs and inheritance. Inheritance in Indonesia is regulated in civil law, customary law and Islamic law depending on where the inheritance system is used based on the area of residence of the person concerned. However, in reality the inheritance system is sometimes not followed or implemented by the community, therefore many problems arise related to the inheritance. The method used in this research is empirical. With the aim of knowing the factors that underlie the control of inheritance by the family and aims to provide options that can be used for people who have an inheritance dispute to choose the process they want to take to resolve inheritance problems, which process is like the settlement process. through outside the judicial route which will produce a win-win solution, but if the outside-judicial route cannot be resolved, then you can use the judicial route which will produce a win-lose solution. It is hoped that the heirs and families can choose a good settlement process and not damage family relations.